(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Elena N. Bekasova (Orenburg, Russian Federation) Ludmila M. Ustyugova (Uzhgorod, Ukraine) On material of 6 most significant Stories of Temporary Years lists the analysis of discrepancies of genetically correlative lexemes breg and bereg is carried out and protected for the purpose of definition of the main directions of their use in the lists differing with the place (the northeast, the West, the southwest and the South of Ancient Russia) and time (the 1417th centuries) of the creation. In all lists dependence of the choice of the correlate defined by origin on thematic features of the text is permanently urgent. At the same time not pleophonic lexeme брегъ without changes remains in contexts of bookSlavic type of language, and the Russicism берегъ is presented in the steady phrases formulas and texts connected with a statement of the events having this or that relation to Novgorod which are characterized by stability of signs East Slavic by origin in all lists. Discrepancies in the use of lexemes breg / bereg are noted first of all in the texts borrowed from other sources and also as a part of prepositional and case designs on брегъ and отъ coast. The analysis of specifics of discrepancies allows to reveal the directions in selection of pleophonic and not pleophonic correlates depending on editorial editing, an orientation of lists and time of their emergence. The research has shown that Old Russian scribes keep the standardized cases of the use of not pleophonic and pleophonic lexemes and consequently also equivalence of their literary status up to the 16th century. However and in more pozdnik lists when the tendency to primary use of not pleophonic correlate amplifies a little, initially developed genetically non-uniform background of the annalistic text remains. Keywords: reflexes the praslavyanskikh of combinations, polnoglasy / nepolnoglasy, the Story of temporary years, lexical discrepancies in lists. DOI 10.23683/1995-0640-2017-2-95-106